2016
DOI: 10.1002/2015jg003019
|View full text |Cite
|
Sign up to set email alerts
|

Estimating daily forest carbon fluxes using a combination of ground and remotely sensed data

Abstract: Several studies have demonstrated that Monteith's approach can efficiently predict forest gross primary production (GPP), while the modeling of net ecosystem production (NEP) is more critical, requiring the additional simulation of forest respirations. The NEP of different forest ecosystems in Italy was currently simulated by the use of a remote sensing driven parametric model (modified C-Fix) and a biogeochemical model (BIOME-BGC). The outputs of the two models, which simulate forests in quasi-equilibrium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 48 publications
3
22
1
Order By: Relevance
“…When the dataset is corrected, the annual rainfall rises to ∼730 mm, and the simulated GPP value approaches 1570 g C m −2 year −1 . This value is somewhat higher than those found for Mediterranean macchia on the island of Pianosa (1050 g C m −2 year −1 , Chiesi et al , ) and in western Sardinia (1140 g C m −2 year −1 , Chirici et al , ), both of which have a drier climate.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…When the dataset is corrected, the annual rainfall rises to ∼730 mm, and the simulated GPP value approaches 1570 g C m −2 year −1 . This value is somewhat higher than those found for Mediterranean macchia on the island of Pianosa (1050 g C m −2 year −1 , Chiesi et al , ) and in western Sardinia (1140 g C m −2 year −1 , Chirici et al , ), both of which have a drier climate.…”
Section: Resultscontrasting
confidence: 53%
“…When the dataset is corrected, the annual rainfall rises to ∼730 mm, and the simulated GPP value approaches 1570 g C m −2 year −1 . This value is somewhat higher than those found for Mediterranean 298 L. Fibbi et al macchia on the island of Pianosa (1050 g C m −2 year −1 , Chiesi et al, 2011) and in western Sardinia (1140 g C m −2 year −1 , Chirici et al, 2015), both of which have a drier climate. Concerning holm oak, the simulated GPP profiles show quite limited seasonal variations that are typical of a Mediterranean evergreen forest (Figure 6(b)).…”
Section: Biome-bgc Simulationsmentioning
confidence: 53%
“…The depth indicated in conventional soil maps, referring to the depth to bedrock, cannot be directly used to drive Biome-BGC. This has been experimentally confirmed for several European sites and often leads to use the standard soil depth (100 cm) for the application of Biome-BGC on a regional scale (Chiesi et al, 2016;Chirici et al, 2015). 2.…”
Section: Discussionmentioning
confidence: 68%
“…This particularly concerns the rooting depth, which directly determines the amount of water available to plants, implying the following relevant considerations: The depth indicated in conventional soil maps, referring to the depth to bedrock, cannot be directly used to drive Biome‐BGC. This has been experimentally confirmed for several European sites and often leads to use the standard soil depth (100 cm) for the application of Biome‐BGC on a regional scale (Chiesi et al, ; Chirici et al, ). Due to their climatic features, Mediterranean areas present a soil water recharge in winter/spring followed by its consumption during summer months (Bolle et al, ). The estimation of soil water storage and its consumption through time is therefore particularly critical in these areas for a correct simulation of water stress impact on vegetation. …”
Section: Discussionmentioning
confidence: 82%
“…However, in Italy, Chirici et al (2016) found NEE values of about 7.0 t C ha -1 y -1 for a beech and a turkey-oak forest at quite different altitudes, and Tirone et al (2003) mention NEE between -5.47 and -6.60 t C ha -1 y for a Q. ilex forest in Castelporziano. It is also interesting to note that similar high values (on the order of -6 t C ha -1 y -1 ) have been reported for forests in northern Europe (Great Britain, sites 20 and 19 in Fig.…”
Section: Resultsmentioning
confidence: 99%